Becoming Citizens in a Changing World: IEA International Civic and Citizenship Education Study 2016 International Report - Schulz, Wolfram (Springer Nature, 2018)
Civic education; ICCS; IEA Educational Achievement; Civic knowledge; Civics and citizenship; Attitudes to civic life; Engagement with civic life; Civic participation